Perilaku Seks Pranikah pada Mahasiswa STIKes Hang Tuah Pekanbaru - Novita Rany (Jurnal Kesehatan Komunitas, 2012)
Based on the resulth of research about premarital sex in 2009 In pekanbaru city by PKBI found that 38,78% of males had ever done extramarital relations and female 16,98%. The study used qualitative method. Subject research was students of STIKes HangTuah collage. To obtain data was by observing and interviewing lecturer in faculties, parents, and owner of hotels. The study found that sex behavior was divided into a no-risk (just talking and holding hands) and risk (from kissing to doing intercourse). From the survey, there were 7 risky informants and 9 not risky. Almost half of informant (7 of 9) behaved sexual. Some of them had ever done matrimony. There were tendencies of relationship in knowledge, attitude, perception, peers and parents roles friendship. STIKes HangTuah and health service suggest that sex education can be one of subject for students.